2019
DOI: 10.4306/jknpa.2019.58.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disabilities Evaluated using World Health Organization Disability Assessment Schedule 2.0 in Patients with Chronic Schizophrenia and Its Related Factors

Abstract: Objectives This study examined the functional disabilities of patients with chronic schizophrenia using WHO Disability Assessment Schedule 2.0 (WHODAS 2.0) and its related factors.Methods The subjects consisted of 86 patients with schizophrenia with more than 10 years' duration of illness and 40 healthy volunteers. The functional disabilities and psychopathology were evaluated using the WHODAS 2.0 and 18-items Brief Psychiatric Rating Scale (BPRS-18), respectively. This study analyzed the six sub-domains ('cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Interestingly, the meta‐analysis results indicated that the app's effectiveness was greater in reducing negative symptoms than positive symptoms of schizophrenia. The majority of schizophrenia patients developed chronic disease 5 to 10 years after the onset of disease (Park et al, 2019) and the participants in the included studies were likely to predominantly experience negative symptoms. The majority of studies used CBT, targeting behavioral motivation by delivering self‐monitoring and various behavioral activation strategies via the apps (Ben‐Zeev et al, 2018; Faurholt‐Jepsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the meta‐analysis results indicated that the app's effectiveness was greater in reducing negative symptoms than positive symptoms of schizophrenia. The majority of schizophrenia patients developed chronic disease 5 to 10 years after the onset of disease (Park et al, 2019) and the participants in the included studies were likely to predominantly experience negative symptoms. The majority of studies used CBT, targeting behavioral motivation by delivering self‐monitoring and various behavioral activation strategies via the apps (Ben‐Zeev et al, 2018; Faurholt‐Jepsen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the tool has low reliability [14] as subjective analysis is possible. In addition, among tools frequently used in clinical practice, it is a general purpose for measuring communication in patients with schizophrenia when the Diagnostic and Statistical Manual of Mental Disorders (DSM -4) is applied using Global Assessment of Functioning (GAF) measures [15]. However, the GAF score is limited in measuring communication because it evaluates various factors such as apathy, communication difficulties, and lack of self-management, which are overall indicators of vocal symptoms with a single score.…”
Section: Original Articlementioning
confidence: 99%
“…In addition, some studies have found differences between subgroups of people with schizophrenia in the WHODAS 2.0 scores by variables such as depression (Akinsulore et al, 2015;Dan et al, 2011;Guilera et al, 2012;McKibbin et al, 2004;Sjonnense et al, 2016;Strassnig et al, 2018), symptomatology (Akinsulore et al, 2015;R. Chen et al, 2019;Ertugrul & Ulug, 2004;Guilera et al, 2012;Park et al, 2019;Strassnig et al, 2018), occupational status (Adegbaju et al, 2013;R. Chen et al, 2019;Guilera et al, 2012;Olagunju et al, 2016;Strassnig et al, 2018;), smoking (Aguocha et al, 2018), gender (Adegbaju et al, 2013), years of education and residence (R. Chen et al, 2019), age (Adegbaju et al, 2013;R.…”
mentioning
confidence: 99%